Final Project Portfolio Sistem Peminjaman Online dan Bebas Pustaka Istek Icsada Bojonegoro / Perencanaan Sistem Informasi Peminjaman Online dan Bebas Pustaka - Suhartini, Andi Mulyanti; Herwidyaningtyas, Frestina Bhakti; Tsani, Margaretta Putri Faradilla; Fahmana, Alvin Eka (Blantika: Multidisciplinary Journal, 2025)
An online book lending information system, developed in the form of a website. This research aims to make it easier for users to borrow books online with a simple but informative interface. This research follows the research flow as the basis for the development and writing of the system, which produces a web-based information system that can be accessed by all circles, both from inside and outside the library. This is expected to increase the use and understanding of library book collections, as well as provide added value for library users and institutions.